PKC/ROS-Mediated NLRP3 Inflammasome Activation Is Attenuated by Leishmania Zinc-Metalloprotease during Infection. - Marina Tiemi Shio; Jan Gregor Christian; Jee Yong Jung; Kwang-Poo Chang; Martin Olivier (PLOS Neglected Tropical Diseases, 2015)
Parasites of the Leishmania genus infect and survive within macrophages by inhibiting several microbicidal molecules, such as nitric oxide and pro-inflammatory cytokines. In this context, various species of Leishmania have been reported to inhibit or reduce the production of IL-1β both in vitro and in vivo. However, the mechanism whereby Leishmania parasites are able to affect IL-1β production and secretion by macrophages is still not fully understood. Dependent on the stimulus at hand, the maturation of IL-1β is facilitated by different inflammasome complexes. The NLRP3 inflammasome has been shown to be of pivotal importance in the detection of danger molecules such as inorganic crystals like asbestos, silica and malarial hemozoin, (HZ) as well as infectious agents. In the present work, we investigated whether Leishmania parasites modulate NLRP3 inflammasome activation. Using PMA-differentiated THP-1 cells, we demonstrate that Leishmania infection effectively inhibits macrophage IL-1β production upon stimulation. In this context, the expression and activity of the metalloprotease GP63 - a critical virulence factor expressed by all infectious Leishmania species - is a prerequisite for a Leishmania-mediated reduction of IL-1β secretion. Accordingly, L. mexicana, purified GP63 and GP63-containing exosomes, caused the inhibition of macrophage IL-1β production. Leishmania-dependent suppression of IL-1β secretion is accompanied by an inhibition of reactive oxygen species (ROS) production that has previously been shown to be associated with NLRP3 inflammasome activation. The observed loss of ROS production was due to an impaired PKC-mediated protein phosphorylation. Furthermore, ROS-independent inflammasome activation was inhibited, possibly due to an observed GP63-dependent cleavage of inflammasome and inflammasome-related proteins. Collectively for the first time, we herein provide evidence that the protozoan parasite Leishmania, through its surface metalloprotease GP63, can significantly inhibit NLRP3 inflammasome ...